Tempos da História: Uma Visão Geral dos Estudos acerca do Tempo Relacionados à Teoria da História (Conceitos, Questões e Tendências) - Cardoso, Hélio Rebello [UNESP]; Mudrovcic, María Inés; Landwehr, Achim (FapUNIFESP (SciELO), 2023)
This article proposes a four-layered diagram that displays as an overview of the current field of historical time studies according to the following branches of investigation: 1) the metaphysics of natural time, 2) the metaphysics of historical time, 3) the regimes of historicity, and 4) historiographical regimes. By defining these fields and their connections, identifying essential concepts, revealing the questions they address, and sketching tendencies that have emerged since the 2000s, this article tackles historical temporality as a theoretical and historiographical subject. This framework, which portrays the state of the art in temporal studies, allows for the presentation and classification of the variety of contributions gathered in this special edition.
TIMES OF HISTORY: An Overview of Time Studies Related to the Theory of History (Concepts, Issues, and Trends)*
Keywords: estudos do tempo; filosofia e teoria da história; history; história; philosophy; tempo; theory of history; time; time studies